Kinerja Keuangan Koperasi Jasa Keuangan Syariah (KJKS) Di Jawa Tengah - Dodik Jatmika; Suhesti Ningsih (Al-Tijary, 2017)
The purpose of this research is to know the financial performance KJKS BMT Mass Group Sragen Central Java and financial position KJKS BMT Mass Group Sragen Central Java. Analysis of research data conducted using three ratios, namely: liquidity, solvency, and profitability. Research data from financial report KJKS BMT Mass Group Sragen Central Java in 2013 and 2014. The results of this study found that: a) liquidity ratio shows liquid in the analysis of Current Ratio of 2013 amounted to 122.01%, while the year 2014 of 153.11%. Then for Cash Ratio analysis show good result; b) solvency ratio of KJKS BMT Mass Group Sragen Central Java shows good results; c) profitability ratios indicate that KJKS BMT Mass Group Sragen Central Java is not rentabel to generate or get maximum net profit.